2018
DOI: 10.1159/000488046
|View full text |Cite
|
Sign up to set email alerts
|

Sepia Ink Oligopeptide Induces Apoptosis of Lung Cancer Cells via Mitochondrial Pathway

Abstract: Background/Aims: Our previous study suggested the anti-tumor activity of sepia ink oligopeptide (SIO). Here we sought to investigate the underlying molecular mechanism. Methods: Cell proliferation was evaluated by cell counting kit-8 (CCK-8) assay. Cell apoptosis was determined by Annexin V/Propidium Iodide (PI) staining. The mitochondria pathway was characterized by quantification of Bcl-2, Bax, Caspase-9 and Cyto-C. The death receptor pathway was analyzed by determinement of Fas, Caspase-8 and NIK. The endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
3
6
0
1
Order By: Relevance
“…Interestingly, peptide B11 treatment caused a decrease in antiapoptotic Bcl-2 protein, but an increase in proapototic Bax in HeLa cells (Figure 5C(ii),(iii)). This observation is similar to that previously reported by Wang et al, where an oligopeptide from Sepia ink induced the apoptosis of lung cancer cells via the mitochondrial pathway [57]. The antiapoptotic Bcl-2 family proteins prevent cell death induced by various apoptotic stimuli by inhibiting the release of mitochondrial cytochrome C, and inhibiting the activation of caspase-9 and caspase-3 [58].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, peptide B11 treatment caused a decrease in antiapoptotic Bcl-2 protein, but an increase in proapototic Bax in HeLa cells (Figure 5C(ii),(iii)). This observation is similar to that previously reported by Wang et al, where an oligopeptide from Sepia ink induced the apoptosis of lung cancer cells via the mitochondrial pathway [57]. The antiapoptotic Bcl-2 family proteins prevent cell death induced by various apoptotic stimuli by inhibiting the release of mitochondrial cytochrome C, and inhibiting the activation of caspase-9 and caspase-3 [58].…”
Section: Discussionsupporting
confidence: 89%
“…Mitochondria are ubiquitous cellular organelles that are responsible for energy metabolism in eukaryotic cells and have been associated with various conditions, including Alzheimer's disease, Parkinson's disease, diabetes mellitus, various cardiovascular diseases, and lung cancer . Mitochondrial DNA mutations and associated disorders are also related to tumor development, growth, angiogenesis, and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of calpain-2 was significantly upregulated when TM induced ERS in human breast cancer cells (Han et al, 2015). Studies have shown that blocking the ERS pathway by ALLN pretreatment can significantly prolong the survival rate of liver cancer cells (Wang et al, 2018a). In this study, immunocytochemical staining results showed that calpain-2 was expressed in the cytoplasm of HSC.…”
Section: Discussionmentioning
confidence: 49%